1993
DOI: 10.1084/jem.178.5.1701
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell receptor expression in immature CD4+CD8+ thymocytes by p56lck tyrosine kinase: basis for differential signaling by CD4 and CD8 in immature thymocytes expressing both coreceptor molecules.

Abstract: SummarySignals transduced through the T cell antigen receptor (TCR) are modulated by the src family tyrosine kinase p56 kk (lck), which associates in mature T cells with the coreceptor molecules CD4 and CD8. Here we describe a novel function oflck in immature CD4+CD8 + thymocytes, that of regulating TCR expression. Activation of lck in immature CD4 + CD8 + thymocytes by intrathymic engagement of CD4 maintains low TCR expression by causing most TCR components to be retained and degraded within the endoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 48 publications
2
99
2
Order By: Relevance
“…2A, the 21-kDa phosphorylated form of TCR- was detected even in freshly prepared CD4 T cells. Endogenously phosphorylated TCR-has been previously reported in splenic T cells (34). In contrast, the hyperphosphorylated 23-kDa TCRwas detectable within 2 min after stimulation and the band intensities were significantly lower in the egg white diet group.…”
Section: Decreased Tyrosine Phosphorylation Of Tcr- Zap-70 and Lat mentioning
confidence: 66%
“…2A, the 21-kDa phosphorylated form of TCR- was detected even in freshly prepared CD4 T cells. Endogenously phosphorylated TCR-has been previously reported in splenic T cells (34). In contrast, the hyperphosphorylated 23-kDa TCRwas detectable within 2 min after stimulation and the band intensities were significantly lower in the egg white diet group.…”
Section: Decreased Tyrosine Phosphorylation Of Tcr- Zap-70 and Lat mentioning
confidence: 66%
“…It directs the double negative to DP transition, is central to the CD4/ CD8 lineage commitment decision (44), and mediates the normal homeostasis of peripheral T cells (45). Wiest et al (44) previously suggested that low TCR levels in DP thymocytes are tied to limiting expression of Lck; the total level of Lck increases in the SP thymocyte in parallel with increases in TCR levels. We postulated that medullary maturation was regulated by the relative accessibility of this newly expressed Lck to different surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The -chain of the TCR-CD3 complex, which is phosphorylated on ITAM motifs in mature T cells upon TCR cross-linking (41) is constitutively phosphorylated at high levels in DP thymocytes (4). phosphorylation is Lck-dependent and results in constitutive association of inactive ZAP70 with phospho- (42,43). These modifications may play a causative role in the low level of surface TCR on DP thymocytes because phosphorylation is linked with TCR internalization in mature cells, and newly synthesized TCR-CD3 complexes in DP thymocytes are targeted for degradation (44).…”
Section: Figurementioning
confidence: 99%